On the convergent validity of two Parental Rearing Behaviour Scales: EIIBU and PBI - Livianos-Aldana, L.; Rojo-Moreno, L. (Acta psychiatrica Scandinavica, 1999)
The EMBU and PBI are two of the most used Parental Rearing Behaviour questionnaires. The literature assumes a high correlation between homonymous and assimilable factors (PBI Care and EMBU Affectional Warmth, PBI Control and EMBU Overprotection). Using a sample of 796 subjects the authors carried out the joint application of both scales in order to determine their concurrent validity. The correlation obtained between the scales barely reaches significance on average levels of correlation. The same can be deduced for the applied Multidimensional Scaling. In conclusion, the most extreme precaution is recommended when considering the homonymous scales of both questionnaires, and their joint use in meta‐analysis is not advised.